Understanding Out-of-Work and Out-of-School Youth in Europe and Central Asia - Mauro, Joseph Anthony; Mitra, Sophie (World Bank, Washington, DC, 2015)
The objectives of this study are to describe and analyze the out-of-work and out-of-school youth (ages 15-24) in the Europe and Central Asia2 (ECA) region. People who are out-of-work and out-of-school are referred to as NEET (Not in Employment, Education or Training). This study attempts to characterize the NEETs by age, gender, education and their activity status. The main findings of this study are listed are as follows: first, the authors find that in the post-2009 period the youth NEET rate for the ECA region was 19.60 percent, which is higher than the OECD youth NEET rate of 16 in 2011 (OECD 2013). Second, this study finds that the NEET rate prior to the financial crisis in 2009 was on the decline, and increased in the post-2009 period. Third, this study finds that the NEET rate for ECA is higher for women than for men for all years. However, since the financial crisis in 2009, the gender gap has declined from 4.64 in pre-2009 to 2.75 percentage points in post-2009, suggesting that young men were more adversely affected by the recession than women. Forth, this study finds that in the ECA region youth males are more often classified as NEETs but active in the labor market, and youth females are more often classified as NEETs but inactive in the labor market. Fifth, using a linear probability model, this study finds that individuals, who are 20-24 years of age, have a lower level of educational attainment and married females are more likely to be NEET. Also, individuals living in urban areas and with lower household sizes are less likely to be NEET. Sixth, another linear probability model was constructed using household budget surveys for six countries in ECA from 2009. The main finding from this model was that NEET youths tend to live in households with lower per capita consumption than their non-NEET counterparts. Seventh, there is an increase in the NEET (unemployed) rate after the crisis, while the NEET (inactive) rate stayed roughly constant.